Development and Implementation of Whole Genome Sequencing-Based Typing Schemes for Clostridioides difficile - Sandra Janezic; Sandra Janezic; Maja Rupnik; Maja Rupnik (Frontiers Media S.A., 2019)
Clostridioides difficile is an important nosocomial pathogen increasingly observed in the community and in different non-human reservoirs. The epidemiology and transmissibility of C. difficile has been studied using a variety of typing methods, including more recently developed whole-genome sequence (WGS) analysis that is becoming used routinely for bacterial typing worldwide. Here we review the schemes for WGS-based typing methods available for C. difficile and their applications in the field of human C. difficile infection (CDI). The two main approaches to discover genomic variations are single nucleotide variant (SNV) analysis and methods based on gene-by-gene comparisons (frequently called core genome or whole genome MLST, cgMLST, or wgMLST). SNV analysis currently provides the ultimate resolution, however, typing nomenclature and standardized methodology are missing. On the other hand, gene-by-gene approaches allow portability and standardized nomenclature, and are therefore becoming increasingly popular in bacterial epidemiology and outbreak investigation. Two commercial software packages (BioNumerics and Ridom SeqSphere+) and an open source database (EnteroBase) for allele and sequence type determination for C. difficile are currently available. Proof-of-concept WGS studies have already enabled advances in the investigation of the population structure of C. difficile species, microevolution within the epidemic strains, intercontinental transmission over time and in tracking of transmission events. WGS of clinical C. difficile isolates demonstrated a considerable genetic diversity suggesting diverse reservoirs for CDI. WGS was also shown to aid in resolving relapses and reinfections in recurrent CDI and has potential for use as a tool for assessing hospital infection prevention and control performance.